Empowering Cartilage Restructuring with Biodegradable Magnesium Doped-Silicon Based-Nanoplatforms: Sustained Delivery and Enhanced Differentiation Potential - Chen M; Liu T; Li W; Li Y; Zhong P; Yan H; Kong J; Liang W (International Journal of Nanomedicine, 2024)
Min Chen,1,* Tao Liu,2,* Wenqiang Li,3 Yingting Li,1 Puxin Zhong,1 Huanchen Yan,1 Jingyin Kong,1 Weixiang Liang2 1Department of Obstetrics and Gynecology, Department of Fetal Medicine and Prenatal Diagnosis; Guangdong Provincial Key Laboratory of Major Obstetric Diseases; Guangdong Provincial Clinical Research Center for Obstetrics and Gynecology; Guangdong-Hong Kong-Macao Greater Bay Area Higher Education Joint Laboratory of Maternal-Fetal Medicine; The Third Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510000, People’s Republic of China; 2Department of Ultrasound; Guangdong Provincial Key Laboratory of Major Obstetric Diseases; Guangdong Provincial Clinical Research Center for Obstetrics and Gynecology; The Third Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510000, People’s Republic of China; 3Engineering Technology Research Center for Sports Assistive Devices of Guangdong, Guangzhou Sport University, Guangzhou, 510076, People’s Republic of China*These authors contributed equally to this workCorrespondence: Min Chen, Email edchen99@gmail.comBackground: Cartilage-related diseases, such as hypoplastic chondrodysplasia a rare genetic disorder that affects newborns, causing abnormal cartilage development and restricted skeletal growth. However, the development of effective treatment strategies for chondrodysplasia still faces significant challenges due to limitations in the controlled drug delivery, biocompatibility, and biodegradability of nanomedicines.Methods: A biodegradable magnesium doped-silicon based-nanoplatforms based on silicon nanoparticles (MON) was constructed. Briefly, the MON was modified with sulfhydryl groups using MPTMS to form MOS. Further engineering of MOS was achieved by incorporating Mg2+ ions through the “dissolution-regrowth” method, resulting in MMOS. Ica was effectively loaded into the MMOS channels, and HA was anchored on the surface of MOS to obtain MMOS-Ica@HA nanoplatforms. Additionally, in vitro cell experiments and in vivo zebrafish embryo models were used to evaluate the effect of the nanoplatforms on cartilage differentiation or formation and the efficiency of treating chondrodysplasia.Results: A series of characterization tests including TEM, SEM, DLS, XPS, EDX, and BET analysis validate the successful preparation of MOS-Ica@HA nanoplatforms. The prepared nanoplatforms show excellent dispersion and controllable drug release behavior. The cytotoxicity evaluation reveals the good biocompatibility of MOS-Ica@HA due to the sustained and controllable release of Ica. Importantly, the presence of Ica and Mg component in MOS-Ica@HA significantly promote chondrogenic differentiation of BMSCs via the Smad5/HIF-1α signaling pathway. In vitro and in vivo experiments confirmed that the nanoplatforms improved chondrodysplasia by promoting cartilage differentiation and formation.Conclusion: The findings suggest the potential application of the developed biodegradable MMOS-Ica@HA nanoplatforms with acceptable drug loading capacity and controlled drug release in chondrodysplasia treatment, which indicates a promising approach for the treatment of chondrodysplasia.Keywords: nanoplatforms, controlled release, biocompatibility, chondrodysplasia, cartilage differentiation